2022
DOI: 10.1249/mss.0000000000003031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6-wk Sprint Interval Training Protocol at Different Altitudes on Circulating Extracellular Vesicles

Abstract: PurposeThis study aimed to investigate the modulation of circulating exosome-like extracellular vesicles (ELVs) after 6 wk of sprint interval training (SIT) at sea level and at 2000, 3000, and 4000 m.MethodsThirty trained endurance male athletes (18–35 yr) participated in a 6-wk SIT program (30-s all-out sprint, 4-min 30-s recovery; 4–9 repetitions, 2 sessions per week) at sea level (n = 8), 2000 m (fraction of inspired oxygen (Fio2) 0.167, n = 8), 3000 m (Fio2 0.145, n = 7), or 4000 m (Fio2 0.13, n = 7). Veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In humans, recent studies investigated whether 12 weeks of resistance exercise training (Xhuti et al., 2023) or 6 weeks of sprint interval training (SIT) (Warnier et al., 2023) altered the presence of small EVs in blood samples taken at rest. The first of these studies observed that a home‐based resistance exercise training intervention (progressive elastic band‐based resistance exercise; 3 days per week) did neither alter the abundance of five EV marker proteins (ALIX, CD63, TSG101, CD9, CD81) nor the size and number of particles in the small EV size range in plasma from older adults taken at ∼96 h after their most recent exercise session (Xhuti et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, recent studies investigated whether 12 weeks of resistance exercise training (Xhuti et al., 2023) or 6 weeks of sprint interval training (SIT) (Warnier et al., 2023) altered the presence of small EVs in blood samples taken at rest. The first of these studies observed that a home‐based resistance exercise training intervention (progressive elastic band‐based resistance exercise; 3 days per week) did neither alter the abundance of five EV marker proteins (ALIX, CD63, TSG101, CD9, CD81) nor the size and number of particles in the small EV size range in plasma from older adults taken at ∼96 h after their most recent exercise session (Xhuti et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The first of these studies observed that a home‐based resistance exercise training intervention (progressive elastic band‐based resistance exercise; 3 days per week) did neither alter the abundance of five EV marker proteins (ALIX, CD63, TSG101, CD9, CD81) nor the size and number of particles in the small EV size range in plasma from older adults taken at ∼96 h after their most recent exercise session (Xhuti et al., 2023). In the second of these studies, endurance‐trained men completed 18 sessions (two sessions per week for 9 weeks) of SIT at either sea level or 2000, 3000 or 4000 m of simulated altitude in the form of normobaric hypoxia (Warnier et al., 2023). There was no effect of exercise training at sea level, but SIT in hypoxia resulted in an increase in the number of particles in the small EV size range (assessed via NTA) in plasma taken at ∼72 h after their last exercise training session (Warnier et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 , 61 Importantly, non-coding RNAs are cell type-specific 62 , 63 but can also exert their functions in other cell types via paracrine and/or endocrine signaling through extracellular vesicles (EVs). 64 66 …”
Section: Exerkines: Exercise-inducible Signaling Moleculesmentioning
confidence: 99%
“…However, sEV isolated from plasma of rowers show elevated systemic miR‐342‐5p concentrations and cardioprotective effects, such as reduced LDH release and cardiomyocyte apoptosis, when injected in human cardiomyocytes subjected to ischemia/reperfusion injury [188]. In contrast, 6‐w SIT enhances the number of circulating EV and the levels of miR‐21‐5p, but decreases miR‐23a‐3p levels under hypoxic conditions [189]. A supervised interval or continuous training for 2 weeks does not alter the number of platelet or leukocytes derived EV in obese adults with prediabetes, whereas dietary sugar intake after training increases the number of endothelial EV, which correlates with improved VO 2max [190].…”
Section: Extracellular Vesicles (Ev)mentioning
confidence: 99%